2005
DOI: 10.1111/j.1471-0528.2005.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased antioxidant enzyme expression and increased oxidative damage in erosive lichen planus of the vulva

Abstract: The aim of this study was to investigate whether increased oxidative stress occurs in erosive lichen planus of the vulva. Skin biopsies from six patients with untreated, histologically confirmed erosive lichen planus of the vulva were examined immunohistochemically using antibodies against antioxidant enzymes. The protein-bound lipid peroxidation products malondialdehyde (MDA) and 4-hydroxynonenale (4-HNE) and the oxidative DNA damage marker 8-hydroxy-2V-deoxyguanosine (8-OHdG) were investigated. Protein carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 9 publications
7
50
0
Order By: Relevance
“…The disease develops through antigen-presentation to CD4+ helper T-cells followed by secretion of different cytokines and activation of CD8+ cytotoxic lymphocytes. During this process, the infl ammatory cells generate various amounts of free radicals and reactive oxygen species (ROS) that damage lipids, proteins and nucleic acids in the surrounding cells (Sander et al, 2005;Khan et al, 2003). In addition keratinocytes can release ROS subsequent to stimulation by proinfl ammatory cytokines and endotoxins (Sander et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease develops through antigen-presentation to CD4+ helper T-cells followed by secretion of different cytokines and activation of CD8+ cytotoxic lymphocytes. During this process, the infl ammatory cells generate various amounts of free radicals and reactive oxygen species (ROS) that damage lipids, proteins and nucleic acids in the surrounding cells (Sander et al, 2005;Khan et al, 2003). In addition keratinocytes can release ROS subsequent to stimulation by proinfl ammatory cytokines and endotoxins (Sander et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative damage and reduced antioxidant defense have been shown in LP of the skin (Sezer et al, 2007) and in the lipids, DNA and proteins that constitute lesional tissues of vulvar lichen planus (Sander et al, 2005). Nitrative and oxidative stresses have been proposed to participate in infl ammatory-mediated carcinogenesis of OLP (Chaiyarit et al, 2005;Sander et al, 2005). A recent population-based case-control investigation evaluated serum levels of antioxidant micronu-trients in patients with this disease.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sirolimus was originally developed as an antifungal agent but this use was abandoned when it was discovered to have potent immunosuppressive and antiproliferative properties. It has been studied for OLP topical management in a small study [88] rapamycin solution (1mg/ml) was applied for three months twice a day in erosive OLP lesions in seven patients; although a patients gave up the study since a burning sensation for the application of sirolimus, after 3 months four patients had total resolution and two a partial remission.…”
Section: Sirolimusmentioning
confidence: 99%
“…Free O2 radicals produced by inducing lipo-peroxidase cause damage to cell membrane and consequently cell apoptosis and necrosis. In one study, a decrease in antioxidant defense and a significant increase in peroxidation products and increased oxidative damage to lipids and DNA and proteins mainly within the basal cell layer of the epidermis and at the dermoepidermal junction, have been demonstrated (Sander et al 2005). One study in 2010 showed the serum level of nitritoxide and superoxide dismutase was greater than control group.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%